2013
DOI: 10.21897/rmvz.158
|View full text |Cite
|
Sign up to set email alerts
|

Modelación del crecimiento de pollitas Lohmann LSL con redes neuronales y modelos de regresión no lineal

Abstract: RESUMEN Objetivo. Modelar la curva del crecimiento de aves de la línea Lohmann LSL utilizando modelos no lineales (MNL), no lineales mixtos (MNLM) y redes neuronales artificiales (RNA). Materiales y métodos.Periódicamente se pesaron 33 aves en promedio, desde el día 21 al 196 de vida para un total de 558 registros individuales de peso. En el ajuste de la curva de crecimiento se utilizaron los modelos: no lineal de Von Bertalanffy (MNL), no lineal Mixto de Von Bertalanffy (MNLM) y redes neuronales artificiales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The result of the study for the model with the lowest values (Galeano-Vasco et al, 2014), as predicted by AIC and BIC, showed that the Von Bertalanffy's growth model had the smallest predicted value in both criteria and the best fit for all the turkey males and local turkey females while Gompertz´s growth model had the best fit for the female exotic and female crossbred turkeys. However, the difference between Von Bertalanffy's and Gompertz's growth models is minimal, thus, making them fit for modeling the growth curve of domestic turkey.…”
Section: Discussionmentioning
confidence: 96%
“…The result of the study for the model with the lowest values (Galeano-Vasco et al, 2014), as predicted by AIC and BIC, showed that the Von Bertalanffy's growth model had the smallest predicted value in both criteria and the best fit for all the turkey males and local turkey females while Gompertz´s growth model had the best fit for the female exotic and female crossbred turkeys. However, the difference between Von Bertalanffy's and Gompertz's growth models is minimal, thus, making them fit for modeling the growth curve of domestic turkey.…”
Section: Discussionmentioning
confidence: 96%
“…An ANN model was developed by Galeano and Cerón [2] to estimate the weight of birds based only on the age of the bird, they found a very good performance with a correlation coefficient (R) of 0.99. The authors recommend the ANN as a viable option for modelling the animal production, because ANN has the ability of new variables inclusion and good adjustment between measured and predicted variables.…”
Section: Introductionmentioning
confidence: 99%